1992
DOI: 10.1210/endo.130.6.1597163
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hepatic angiotensinogen synthesis and secretion by steroid hormones.

Abstract: The regulation of angiotensinogen gene expression by steroid hormones in the rat liver has been examined. In the intact animal, dexamethasone (7 mg/kg ip) and estradiol (7 mg/kg sc) caused an increase in plasma angiotensinogen, which became first apparent after 5 or 9 h, respectively, and resulted in plasma concentrations 4.6- and 1.9-fold higher than in controls at 24 h. These changes were preceded by comparable increases in hepatic angiotensinogen messenger RNA (mRNA). In contrast, dihydrotestosterone (10 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 26 publications
2
33
1
Order By: Relevance
“…Previous studies have reported a higher plasma Agt concentration in women, especially in the homozygotes for the T allele at the AGT M235T locus (17). The promoter region of the AGT gene contains an estrogen responsive element (17) and estrogen has been shown to enhance Agt production both in humans (37,38) and animals (39). Thus, the gender differences observed in the present study may have a real physiological basis rather than being simply the result of spurious statistical observations.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have reported a higher plasma Agt concentration in women, especially in the homozygotes for the T allele at the AGT M235T locus (17). The promoter region of the AGT gene contains an estrogen responsive element (17) and estrogen has been shown to enhance Agt production both in humans (37,38) and animals (39). Thus, the gender differences observed in the present study may have a real physiological basis rather than being simply the result of spurious statistical observations.…”
Section: Discussionmentioning
confidence: 72%
“…The synthesis of angiotensinogen in hepatocytes is regulated by estrogens (11). Plasma renin levels and angiotensin-converting enzyme (ACE) activity are significantly higher in estrogen-deficient compared with estrogen-replete rats and in postmenopausal women not receiving HRT compared with women on HRT (9,12).…”
mentioning
confidence: 99%
“…Estrogens influence the rennin-angiotensin system by regulating the synthesis of angiotensinogen in hepatocytes (17). Plasma rennin levels and angiotensin-converting enzyme activity are significantly higher in estrogen-deficient versus estrogen-replete rats, and in postmenopausal women not receiving hormone replacement therapy (HRT) versus those receiving it (18,19).…”
mentioning
confidence: 99%